1
$\begingroup$

How to find the limit of the sequence with $n^{th}$ term $$x_n = \left(\frac{2n+3}{n^2}\right)^n$$

Is it possible to apply l'Hôpital's rule in this case?

$\endgroup$
6
$\begingroup$

Limit going to what? If $n \to \infty$, a number less than $\frac12$ is raised to a high power so it goes rapidly to $0$.

$\endgroup$
2
  • 2
    $\begingroup$ Yes? $(1-\frac{1}{n})^n$ :-) $\endgroup$
    – Listing
    Dec 21 '11 at 0:30
  • $\begingroup$ @Listing: true, but here it doesn't go to $1^\infty$. I'll update. $\endgroup$ Dec 21 '11 at 1:01
2
$\begingroup$

As usual when the variable appears in the exponent, write it using the rule $a^b = \exp(b \ln a)$ :

$$\exp\left( n \ln\left({2n + 3 \over n^2}\right)\right)$$ and $$n \ln\left({2n + 3 \over n^2}\right) = n\ln(2n+3) - 2n\ln(n) = n\ln(n)\left( \ln\left(2+{3\over n}\right)-2 \right). $$ It is now easy to conclude: $n \ln(n) \mathop\longrightarrow\limits_{n\rightarrow\infty} \infty$ and $ \ln\left(2+{3\over n}\right)-2\mathop\longrightarrow\limits_{n\rightarrow\infty} \ln 2 -2 < 0$, so $n \ln\left({2n + 3 \over n^2}\right) \mathop\longrightarrow\limits_{n\rightarrow\infty} -\infty$ and $ \exp\left( n \ln\left({2n + 3 \over n^2}\right)\right) \mathop\longrightarrow\limits_{n\rightarrow\infty} 0$.

To have a chance to apply l’Hospital rule, try to put $x = 1/n$ and study the limit in 0, but I think this is not very useful here, as the above method is rather straightforward.

$\endgroup$
0
$\begingroup$

well:

$$\left(\frac{2n+3}{n^2}\right)^n=e^{n\ln{\frac{2n+3}{n^2}}}$$

so:

$$\lim_{n \to+\infty}n\ln{\frac{2n+3}{n^2}}$$

$\endgroup$
1
  • $\begingroup$ So... e raised to that power?? $\endgroup$ Dec 21 '11 at 2:19
0
$\begingroup$

Find a sequence $y_n$ such that $x_n \leq y_n$ and $\lim\limits_{n \to \infty} y_n = 0$. Since $0 \leq x_n \forall n$, then we can write $0 \leq \lim\limits_{n \to \infty} x_n \leq \lim\limits_{n \to \infty} y_n = 0$ and it follows that $\lim\limits_{n \to \infty} x_n = 0$. One such sequence is $5/n$ for $n > 5$.

$\endgroup$
0
$\begingroup$

Let $y=\big(\frac{2n+3}{n^2}\big)^n$, so $\ln y= n\ln \big(\frac{2n+3}{n^2}\big)$. Since $\displaystyle\lim _{n\rightarrow\infty}n\ln(\frac{2n+3}{n^2})=-\infty$, we have $\displaystyle\lim _{n\rightarrow\infty} y=0.$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.